Computational evaluation of the biomechanical effects of position changes in the femoral neck system on Pauwels type III femoral neck fractures: an in silico study - Zhang, Xiang; Zhang, Shenghang; Zhong, Zhou; Zhang, Wen; Xiong, Zhongwei (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionDespite the biomechanical advantages of the Femoral Neck System (FNS), improvements in postoperative complication rates have not been significant. This study evaluated the effects of different FNS positions on the biomechanical stability of Pauwels type III femoral neck fractures (FNFs) using finite element analysis (FEA).MethodsPauwels type III FNF models fixed with different FNS positions were constructed using various bolt lengths, bolt positions, and axis–bolt angles. Biomechanical parameters, including stiffness, maximum implant von Mises stress (MIVS), maximum interfragmentary shear stress (MISS), and maximum interfragmentary gap (MIG), were analyzed by simulating early postoperative weight-bearing. Entropy scoring was used to rank the performance of different fixation positions to determine the optimal FNS implantation position.ResultsCompared with that of the standard model, the biomechanical stability changed when FNS positioning was altered. Among all the evaluated parameters, MIG had the highest weight (60.04%). In the lateral view, fracture fixation was most stable when the bolt was rotated 5° anteriorly relative to the femoral neck axis (composite score = 0.87). However, stability was poorer when the bolt was rotated 9° inward relative to the femoral neck axis (composite score = 0.13).DiscussionThe MIG is an important biomechanical parameter for assessing the stability of different FNS positions when treating FNFs. Shortening the distance between the bolt and the subchondral bone, upward movement, external rotation, and anterior rotation of the bolt can help improve the stability of the FNS in the treatment of Pauwels III FNFs.